Clement of Alexandria and the shaping of Christian literary practice: miscellany and the transformation of Greco-Roman writing - Heath, Jane M. F. (Cambridge University Press, 2020)
"Clement of Alexandria's Stromateis were celebrated in antiquity but modern readers have often skirted them as a messy jumble of notes. When scholarship on Greco-Roman miscellanies took off in the 1990s, Clement was left out as 'different' because he was Christian. This book interrogates the notion of Clement's 'Christian difference' by comparing his work with classic Roman miscellanies, especially those by Plutarch, Pliny, Gellius and Athenaeus. The comparison opens up fuller insight into the literary and theological character of Clement's own oeuvre. Clement's Stromateis are contextualised within his larger literary project in Christian formation, which began with the Protrepticus and the Paedagogus and was completed by the Hypotyposeis. Together, this stepped sequence of works structured readers' reorientation, purification and deepening prayerful 'converse' with God. Clement shaped his miscellanies as an instrument for encountering the hidden God in a hidden way, while marvelling at the variegated beauty of divine work refracted through the variegated beauty of his own textuality"--